Studi Tentang Pengaruh Ajaran Islam pada Perekonomian Negara Arab Saudi - Diva Nazmi Laila; Della Wahyuningsih; Apriyanto Apriyanto; Mohammad Ridwan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Saudi Arabia is a country that uses the Qur’an and Sunnah as the foundation of its constitution, which makes Islamic teachings significantly influential across various sectors of life, including the economic sector. This study aims to analyze the influence of Islamic teachings on the development of the Saudi Arabian economy and examine how the country addresses the challenges of modernization and economic globalization. The research employs a library research method with a qualitative descriptive approach. The findings indicate that Islamic teachings play a central role in shaping economic policies in Saudi Arabia, guiding both regulatory frameworks and development directions. However, the country’s strong dependence on the oil and gas sector has become a major structural challenge in achieving sustainable economic growth. In response, the Saudi government has implemented economic reforms through the Vision 2030 program, which is designed to diversify the national economy beyond oil dependency. These reforms reflect a strategic effort to balance the preservation of Islamic values with the need to adapt to global economic changes and modernization demands. Overall, the study highlights the dynamic interaction between religious principles and economic transformation in Saudi Arabia’s development strategy.